Effectiveness of inactivated hantavirus vaccine on the disease severity of hemorrhagic fever with renal syndrome - Yongjin Yi; Hayne Park; Jaehun Jung (The Korean Society of Nephrology, 2018)
Background : An inactivated Hantaan virus vaccine (iHV) has been broadly used as a preventive strategy for hemorrhagic fever with renal syndrome (HFRS) by the South Korean Army. After the vaccination program was initiated, the overall incidence of HFRS cases was reduced in the military population. While there are about 400 HFRS cases annually, few studies have demonstrated the efficacy of the iHV in field settings. Therefore, this study aimed to evaluate the iHV efficacy on HFRS severity. Methods : From 2009 to 2017, HFRS cases were collected in South Korean Army hospitals along with patients vaccination history. HFRS patients were classified retrospectively into two groups according to vaccination records: no history of iHV vaccination and valid vaccination. Vaccine efficacy on the severity of acute kidney injury (AKI) stage and dialysis events were investigated. Results : The effects of the iHV on renal injury severity in between 18 valid vaccinated and 110 non-vaccinated patients were respectively evaluated. In the valid vaccination group, six of the 18 HFRS patients (33.3%) had stage 3 AKI, compared to 60 of the 110 (54.5%) patients in the non-vaccination group. The iHV efficacy against disease progression (VEp) was 58.1% (95% confidence interval, 31.3% to 88.0%). Conclusion : The iHV efficacy against the progression of HFRS failed to demonstrate statistically significant protection. However, different severity profiles were observed between the iHV and non-vaccination groups. Additional studies with larger populations are needed to demonstrate the effectiveness of the iHV in patients with HFRS.